Medicinal Traits of the Phenolic Compound from Foeniculum vulgare for Oligomenorrhea - Javesh Patil; Devyani Patil; Hamid Sayyed; Mamta Patil; Ravindra Mali (Chemistry Proceedings, 2022)
A phenolic compound in Foeniculum vulgare can improve human health. Foeniculum vulgar contains flavonoids, glycosides, and other constituents that are used for medicinal ailments. Trans-anethole, fenchone, and estragole essential oils are the main ingredients in F. vulgare seeds. The principle component of fennel oil, anethole, has structural similarity with the synthetic oestrogen diethylstilbestrol, making it an active estrogenic agent. Women with PCOS may exhibit obesity, amenorrhea, oligomenorrhea, infertility, or androgenic features, which are characterized by the absence of ovulation and hyperandrogenism. Oligomenorrhea is a kind of irregular menstruation period. Treatment of oligomenorrhea depends on the causes; the main cause of oligomenorrhea is the presence of polycystic ovarian syndrome (PCOS), with 75–85%experiencing infrequent periods. This mini-review focuses on F. vulgare seeds as an advantageous addition to treat PCOS. Women with PCOS also have a lower level of the hormone progesterone due to the absence or reduction in ovulation. Numerous phytoestrogens can be found in F.vulgare seeds; with less insulin resistance and lower blood sugar level, fennel phytoestrogen content is beneficial. It is also thought to aid in reducing the cellularim balance that causes PCOS’s metabolic abnormalities.